Ewolucja relacji międzykulturowych w erze transformacji technologicznych .......... 47 - Jaskuła-Korporowicz, Sylwia (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
THE EVOLUTION OF INTERCULTURAL RELATIONS IN THE ERA OF TECHNOLOGICAL TRANSFORMATIONThe contemporary world is undergoing dynamic changes, which, in an era of increasing cultural diversity, are exerting an ever-stronger influence on the nature and scope of today’s intercultural relations. Globalization, rapid technological development, migrations, and growing cultural interactions are becoming key factors shaping modern societies. In the context of these transformations, building theories of intercultural relations, as contributed to the social sciences and cultural studies by Professor Tadeusz Paleczny, constitutes a crucial analytical tool for understanding and interpreting the complexities of contemporary interactions and the interpenetration of cultures.